High-fat Diet Enhances Gastric Contractility, but Abolishes Nesfatin-1-induced Inhibition of Gastric Emptying - YEGEN, BERRAK; YÜKSEL, MERAL; KAYA, ÖZLEM TUĞÇE; ARABACI TAMER, SEVİL; KOYUNCUOĞLU, TÜRKAN (KOREAN SOC NEUROGASTROENTEROLOGY & MOTILITY, 2021)
Neither HFD nor NES-1 changed methylcellulose emptying, but NES-1 delayed saline emptying in cannulated ND-rats. Inhibitory effect of NES-1 on gastric emptying in ND-rats was reversed by all antagonists, and abolished in HFD-rats. In HFD-rats, carbachol-induced contractility was enhanced in gastric, but inhibited in ileal strips. HFD increased body weight, while serum triglycerides, alanine transaminase, aspartate aminotransferase, glucose, and levels of malondialdehyde, glutathione, myeloperoxidase activity, and luminolchemiluminescence in hepatic, ileal, and adipose tissues were similar in ND- and HFD-rats, but only lucigenin-chemiluminescence was Background/Aims Gastrointestinal motility changes contribute to development and maintenance of obesity. Nesfatin-1 (NES-1) is involved in central appetite control. The aim is to elucidate effects of NES-1 and high-fat diet (HFD) on gastrointestinal motility and to explore myenteric neuron expressions of tyrosine hydroxylase (TH), vasoactive intestinal peptide (VIP), and neuronal nitric oxide synthase (nNOS) in HFDinduced oxidative injury. Methods Sprague-Dawley rats were fed with normal diet (ND) or HFD. Gastric emptying rate was measured following NES-1 (5 pmol/rat, intracerebroventricular) preceded by subcutaneous injections of glucagon-like peptide 1 (GLP-1), cholecystokinin 1 (CCK-1), and gastrin/CCK-2 receptor antagonists. In carbachol-contracted gastric and ileal strips, contractile changes were recorded by adding NES1 (0.3 nmol/L), GLP-1, CCK-1, and gastrin/CCK-2 antagonists. Results Neither HFD nor NES-1 changed methylcellulose emptying, but NES-1 delayed saline emptying in cannulated ND-rats. Inhibitory effect of NES-1 on gastric emptying in ND-rats was reversed by all antagonists, and abolished in HFD-rats. In HFD-rats, carbachol-induced contractility was enhanced in gastric, but inhibited in ileal strips. HFD increased body weight, while serum triglycerides, alanine transaminase, aspartate aminotransferase, glucose, and levels of malondialdehyde, glutathione, myeloperoxidase activity, and luminolchemiluminescence in hepatic, ileal, and adipose tissues were similar in ND-and HFD-rats, but only lucigenin-chemiluminescence was increased in HFD-rats. Vasoactive intestinal peptide (VIP) and TH immunoreactivities were depressed and nNOS immunoreactivity was increased in gastric tissues of HFD-rats, while VIP and TH were enhanced, but nNOS was reduced in their intestines. Conclusions HFD caused mild systemic inflammation, disrupted enteric innervation, enhanced gastric contractility, inhibited ileal contractility, and eliminated inhibitory effect of NES-1 on gastric motility. (J Neurogastroenterol Motil 2021;27:265-278)
Keywords: Cholecystokinin; Gastric emptying; Nesfatin-1; Nitric oxide synthase type I; Vasoactive intestinal peptide; DISTENSION-SENSITIVE NEURONS; GLUCAGON-LIKE PEPTIDE-1; CHOLECYSTOKININ; INFLAMMATION; SECRETION; RECEPTOR; MOTILITY; SATIETY; OBESITY; RAT